Ossified democracy as an economic problem and policies for reclaiming its performance - Vladimír Benáček; Pavol Frič (Charles University in Prague, Institute of Economic Studies (IES), 2023)
This paper analyses the erosion of democracy in the countries of Central and Eastern Europe from the perspective of political economy. We posit that the coinciding effects of political marketing and the state financing of parties represent a peculiar mix of liberal and étatist principles that have turned political regimes in the region into ossified democracies. Our theoretical analysis based on the economics of democracy of Anthony Downs revealed that voters are discriminated against as political consumers, which constrains their ability to function as sovereign principals in collective action. The dominance of political parties in the markets for both political and public goods is the leading cause of democracy's ossification and its susceptibility to corruption. We propose attenuating this decline through mandatory political tax designations, which re-establish the lost link between political markets and the markets in public goods and make the top-down dominance of the hierarchies in power subject to the bottom-up control of citizens motivated to engage in collective action. Economics of democracy is a heterogeneous fusion of market and command economy.
Keywords: D73; D78; H4; 330; public goods; democracy; collective action; political markets; financing ofparties